2013
DOI: 10.1137/120874655
|View full text |Cite
|
Sign up to set email alerts
|

Reducibility among Fractional Stability Problems

Abstract: Abstract"As has often been the case with NP-completeness proofs, PPAD-completeness proofs will be eventually refined to cover simpler and more realistic looking classes of games. And then researchers will strive to identify even simpler classes." -Papadimitriou (chapter 2 of [37])In a landmark paper [39], Papadimitriou introduced a number of syntactic subclasses of TFNP based on proof styles that (unlike TFNP) admit complete problems. A recent series of results [12,19,6,7,8,9] has shown that finding Nash equil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Only recently Laoutaris et. al [39] studied the fractional bounded budget connection games and Kintali et al [51] studied the complexity of Nash equilibria in such games.…”
Section: Related Workmentioning
confidence: 99%
“…Only recently Laoutaris et. al [39] studied the fractional bounded budget connection games and Kintali et al [51] studied the complexity of Nash equilibria in such games.…”
Section: Related Workmentioning
confidence: 99%
“…In the case of PPAD this is the parity argument on a directed graph, equivalent to the existence guarantee of Brouwer fixpoints: a Brouwer function is a continuous function f : D → D where D is a convex compact domain, and Brouwer's fixed point theorem guarantees a point x for which f (x) = x. PPAD has been widely used to classify problems of computing game-theoretic equilibria (a long line of work on Nash equilibrium computation beginning with Daskalakis et al [2009]; Chen et al [2009b] and market equilibria, e.g., Chen et al [2009a]). PPAD also captures diverse problems in combinatorics and cooperative game theory [Kintali et al, 2013].…”
Section: Np Total Search Classes: Ppad Pls and Clsmentioning
confidence: 99%
“…Kintali et al [8] showed that finding a stable fractional hypergraph matching is PPAD-complete. We reduce this problem to the stable multicommodity flow problem in order to prove the following theorem.…”
Section: Ppad-hardnessmentioning
confidence: 99%